2011
DOI: 10.7196/samj.4078
|View full text |Cite
|
Sign up to set email alerts
|

Loss to follow-up in a community clinic in South Africa - roles of gender, pregnancy, and CD4 count

Abstract: Background Faith-based organizations have expanded access to antiretroviral therapy (ART) in community clinics across South Africa. Loss to follow-up (LTFU), however, limits both the potential individual and population treatment benefits and is an obstacle to optimal care. Objective To identify patient characteristics associated with LTFU six months after starting ART in patients in a large South African community clinic. Methods Patients initiating ART between April 2004 and October 2006 in one Catholic R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 8 publications
5
74
2
Order By: Relevance
“…Although patients were selected on the basis of at least 1 clinical visit or laboratory follow-up, the drop-out incidence remained low, particularly in comparison with other recent observations that have shown rates of 20 dropouts per 100 person-years [37] or the loss to follow-up of 7%-8% of patients at 6-8 months after ART initiation [3,38]. This is probably the result of the active adherence implementation and of active patient followup in this program (see Patients and Methods) [37].…”
Section: Discussionmentioning
confidence: 98%
“…Although patients were selected on the basis of at least 1 clinical visit or laboratory follow-up, the drop-out incidence remained low, particularly in comparison with other recent observations that have shown rates of 20 dropouts per 100 person-years [37] or the loss to follow-up of 7%-8% of patients at 6-8 months after ART initiation [3,38]. This is probably the result of the active adherence implementation and of active patient followup in this program (see Patients and Methods) [37].…”
Section: Discussionmentioning
confidence: 98%
“…Lost-to-follow-up rates of between 5% and 15% are not uncommon in research and community clinic settings in South Africa. 11,12 From a public health perspective, the need for strengthening hospital record-keeping, as well as the human resources to improve service delivery, is exposed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies from South Africa, however, indicate that pregnant women are more likely to be lost to follow-up (LTFU) compared with their nonpregnant counterparts. 22,23 One study comparing LTFU rates over 3 years between pregnant and nonpregnant women who were referred to an antiretroviral treatment center found that pregnant women had higher LTFU, and this continued throughout the follow-up period. This suggests that influences affecting follow-up extend beyond the immediate postpartum period.…”
Section: Discussionmentioning
confidence: 99%